Anti-interleukin-4 modulation of the Th2 polarized response to the parasitic nematode Brugia pahangi. - Osborne, J (1996)
Lymphatic filariasis is a chronic disease characterized by a pronounced Th2 bias in the immune response and impaired antigen (Ag)-specific Th1 responses. We have used a mouse model of filariasis to investigate the role of the infective form (the third-stage larvae [L3]) in modulating the immune response. Subcutaneous infection of BALB/c mice with L3 of Brugia pahangi has a profound effect on Th cell function. By day 12 post-infection, spleen cells from these mice exhibited a dramatic reduction in concanavalin A-driven proliferation and interleukin-2 (IL-2) and gamma interferon (IFN-gamma) secretion in comparison with uninfected controls. However, exposure to L3 did not render the mice completely unresponsive; these animals mounted a strong Th2 response to the parasite, characterized by elevated levels of IL-4, IL-5, and IL-10 and parasite-specific serum immunoglobulin G (IgG), IgG1, and IgE. Treatment of spleen cells from L3-infected mice with neutralizing anti-IL-4 or recombinant IL-2 resulted in a dramatic increase in concanavalin A-induced proliferation and IL-2 and IFN-gamma production. Despite their defective polyclonal Th1 response, cells from L3 infected mice proliferated when stimulated with Ag, and this response was blocked by anti-IL-4. However, anti-IL-4 treatment failed to induce Ag-specific IL-2 or IFN-gamma production, indicating that B.pahangi-primed Th1 cells do not appear to be present or are still unable to respond even in the absence of IL-4.